Two-dimensional material-based complementary ambipolar field-effect transistors with ohmic-like contacts - Park, Jimin; Son, Jangyup; Park, Sang Kyu; Lee, Dong Su; Jeon, Dae-Young (Institute of Physics Publishing, 2023)
Ambipolar field-effect transistors (FETs) possessing both electron and hole carriers enable implementation of novel reconfigurable transistors, artificial synaptic transistors, and output polarity controllable (OPC) amplifiers. Here, we fabricated a two-dimensional (2D) material-based complementary ambipolar FET and investigated its electrical characteristics. Properties of ohmic-like contacts at source/drain sides were verified from output characteristics and temperature-dependent measurements. The symmetry of electron and hole currents can be easily achieved by optimization of the MoS2 or WSe2 channels, different from the conventional ambipolar FET with fundamental issues related to Schottky barriers. In addition, we demonstrated successful operation of a complementary inverter and OPC amplifier, using the fabricated complementary ambipolar FET based on 2D materials.